Motivasi Intrinsik dalam Organisasi Mahasiswa: Peran Organizational Belonging dan Social Support - Permata Ayu; Jimmy Ellya Kurniawan (IDEA: Jurnal Psikologi, 2026)
This study aims to examine the effect of organizational belonging and social support on intrinsic motivation among student organization administrators. The research subjects consisted of 109 students who served as administrators of organizations at a private university in Indonesia. Using a quantitative approach, data were collected through the Intrinsic Motivation Inventory (IMI), Organizational Belonging Scale, and ENRICH Social Support Instrument (ESSI). Multiple linear regression analysis was used to test the predictive contribution of each variable. The results showed that organizational belonging and social support simultaneously explained 45.3% of the variation in intrinsic motivation (R² = 0.453, p < .001), thus accepting the major hypothesis. However, in accordance with the minor hypothesis testing, only organizational belonging had a significant effect (β = 0.652, p < .001), while social support did not have a significant effect in the model (β = 0.031, p = 0.744). Stepwise analysis confirmed that organizational belonging is the strongest single predictor. These findings highlight the importance of strengthening a sense of belonging to increase the intrinsic motivation of organizational administrators.